The enunciation of the image as a presentation practice. Anthropo-semiotic perspectives - Fontanille, Jacques (E|C, 2020)
The history of the concept of enunciation is short, non-linear, and marked both by linguistic and verbal domination, and by the reduction of the principle of immanence to textuality. This is one of the semiotic issues where the divergences are the most marked, especially within structural semiotics.